2016
DOI: 10.7863/ultra.16.01042
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sonography for Evaluation of Gastrointestinal Foreign Bodies

Abstract: Foreign body ingestion is frequently encountered in children. The locations of the foreign bodies and the period during which they have been present in the thorax and abdomen are important for determining the method and timing of treatment. Although plain radiography and computed tomography are primarily used for assessment of foreign bodies, sonography without radiation is also useful for diagnosis of foreign bodies. This report describes 5 cases of foreign bodies in the digestive tract and the usefulness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…However, recently, PVG was de-tected in not only pediatric patients with life-threatening conditions, such as ischemia or necrotizing enterocolitis (NEC) [1,8,9], but also in those without life-threatening conditions such as patients who received post-hematologic stem cell transplantation, immunosuppressive therapy, chemotherapy and those with bowel inflammation, food allergies and disease or trauma of the hepatobiliary system [9][10][11][12][13][14][15]. exposure or sedation; additionally, it can be readily and repeatedly performed at the patient's bedside [9,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, recently, PVG was de-tected in not only pediatric patients with life-threatening conditions, such as ischemia or necrotizing enterocolitis (NEC) [1,8,9], but also in those without life-threatening conditions such as patients who received post-hematologic stem cell transplantation, immunosuppressive therapy, chemotherapy and those with bowel inflammation, food allergies and disease or trauma of the hepatobiliary system [9][10][11][12][13][14][15]. exposure or sedation; additionally, it can be readily and repeatedly performed at the patient's bedside [9,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…These offer less radiation than CT. Radiography is an accessible service and lateral and anteroposterior views are useful when a radiopaque foreign body cannot be located on oropharyngeal examination or flexible nasendoscopy 10. Sonography has been reported for use in paediatric cases for localisation of gastrointestinal foreign bodies 11. CT however is a useful and arguably superior tool, not only for identification of ingested fish bones12 13 but also for assessment of any complications from ingestion, as demonstrated in this case study.…”
Section: Discussionmentioning
confidence: 76%
“…Although previous studies have not recommended US for detecting ingested foreign bodies due to lack of sufficient evidence [ 3 4 5 ], several studies have reported its usefulness in assessing foreign bodies located in the GI tract [ 2 6 7 ]. US provides real-time imaging with superior temporal and spatial resolutions compared to plain radiography and CT with the precision of the ingested foreign body localization, particularly in young children with small body habitus.…”
Section: Discussionmentioning
confidence: 99%